HABITUS TOKOH DAVID DALAM NOVEL A CHILD CALLED IT DAN THE LOST BOY KARYA DAVE PELZER - ADELINE GRACE MARIANNE LITAAY; DHENY JATMIKO (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
Habitus is a concept from Pierre Bourdie (1977), which is agent’s structural base in conducting practices or actions This study is focused on habitus and the construction structure in David, the main character in Dave Pelzer’s A Child Called It and The Lost Boy. Habitus is shown in David’s actions and attitude when dealing with people around him. The method used in this research is descriptive method, which aims to objectively describe the subject which is the subject of science by collecting basic descriptive information needed to understand the nature of the subject. The study reveals that David’s habitus includes low self esteem, inferior feeling, continuous suspicious and difficulties to trust others, rude utterances and theft; which are the results of internalization of his alcoholic and rude mom’s parenting style. David’s mother treated him cruelly; which ranges from physical abuse (hit, stabbed with a knife, and burned), psychological abuse (threat and forced to say bad things about himself), and neglect (left starving, hurt, and isolated). Keywords: habitus, physical abuse, psychological abuse